(untitled) (Fiep Bulletin - online, 2013)
When we speak of society, in a generalized manner, in them let us tie to the individuals, groups, public, and mass, multitude, agglomerated. With relation Brazilian and Argentine society - this common collection of individuals for many is peculiar for me. I question if it has a Social Theory to explain the Brazilian and Argentine society tied with the sport. As we cannot leave of side - the soccer - this equal condition of sport and it leads to an implacable theorization and many times (DES) harmonious when related to the concepts of status - habitus - configurations - that is, the theory is symbolic. Of what we want to designate of more important enters the authors of “Condition Human being” (Hannah Arendt), “the Conquest of the Gift”, “In the deep one of the Appearances” (Michel Maffesoli), “Society of the Individuals” and “Symbolic Theory” (Norbert Elias) is to try to understand the construction of the “Brazilian being” and “to be Argentine”, on what the involvement of the sport is based - soccer. The mediate arguments are innumerable, however, the epistemological spacing between them finish in journalistic emperies e, the scientific analogies break of theories hygienists of the history of the Physical Education as facts and confirmed analytical data sociological, however, the explanation of the Brazilian character pushes for innumerable ways that they collate with the Argentine.